Quercetin alleviates gold nanoparticles-induced hepato-renal toxicity: roles of oxidative stress, inflammation, and histopathology - Mohammed Y. I. Al-Hamadani; Mokhtar I. Yousef; Wael M. El-Sayed (Journal of Basic and Applied Zoology)
Abstract Background Gold nanoparticles (AuNPs) are increasingly used in biomedical applications, but concerns regarding their potential toxicity, particularly in the liver and kidneys, have been raised. This study aims to investigate the protective effects of quercetin (Qu), a potent antioxidant, against AuNP-induced hepato-renal toxicity in male mice. Methods Male mice were treated with AuNPs (4 mg/kg), Qu (15 mg/kg), or a combination of both for 14 days. Body weight changes, organ weights, histopathological alterations, and biochemical markers of oxidative stress and inflammation were assessed. Histological examinations were conducted on liver and kidney tissues, and levels of tumor necrosis factor-alpha (TNF-α), superoxide dismutase (SOD), and reduced glutathione (GSH) were measured in tissue homogenates. Results Significant increases in body, liver, and kidney weights were observed in the AuNP-treated group, indicating potential toxicity. Histopathological analysis revealed liver damage, including inflammatory cell infiltration and hepatocyte necrosis, along with kidney injury characterized by mesangial hyperplasia and tubular degeneration. The combination of AuNPs and Qu led to a reduction in these pathological changes. Additionally, AuNP treatment significantly elevated TNF-α levels, whereas Qu effectively reduced TNF-α levels, suggesting its anti-inflammatory properties. AuNPs induced oxidative stress by altering antioxidant enzyme activities, while Qu mitigated these effects by normalizing SOD and GSH levels. Conclusions Quercetin demonstrated ameliorative effects against AuNP-induced hepato-renal toxicity, mitigating oxidative stress, inflammation, and histopathological damage. These findings highlight quercetin’s potential as a therapeutic agent for reducing gold nanoparticle-induced toxicity, especially in liver and kidney tissues.